Monoclinic - Tetragonal Zirconia quantification of commercial nanopowder mixtures by XRD and DTA - Gauna, Matías Roberto (2015)
The phase quantification in ceramic nanopowders presents technological interest for studying and design purposes. Especially in zirconia ceramics where the mechanical and transport properties are strongly affected by the crystalline composition. In this work we present the comparison XRD based methods and differential thermal analysis methods for phase characterization and specially quantification. A complete series of commercial nanopowders mixtures (D50 ≈ 0.1 um) of monoclinic zirconia (m) and partially stabilized zirconia (t: 3 % yttrium oxide) was studied. X ray diffraction (XRD) was performed and the relation m:t was quantified by the so called Garvie-Nicholson (G-N), Toraya and Rietveld method. A complete reversible DTA analysis was carried out to the same mixtures. Both m-t and t-m martensitic thermal transformations were observed and pondered for the m-ZrO2 containing samples. The graphical integration was performed and employed for the construction of a calibration curve in the studied composition range. The results were compared, the Toraya method presented equivalent results in comparison with the Rietveld method. The G-N method presented appreciable differences (≈ 10 %). To assume a direct proportion of the m-ZrO2 content with the peak area resulted in important errors but if a simple calibration curve is constructed, the DTA method presents accurate quantification with results comparable to the best XRD based quantification.